Public and private sector takes Climate-Smart Village scaling to next level in India and Nepal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
State governments in India/Nepal and private sector corporates in India are increasingly giving emphasis on scaling of Climate Smart Villages (CSVs) for building climate-resilient agriculture. The scaling activities through government efforts build on existing CSVs and the new initiatives are either focusing on increased investments and expanding it to new villages. The private sector initiatives in India focus on working with ITC limited, Reliance Foundation and Sonalika Foundation. The impact assessment of CSV projects is also being done.